Associations of erythrocyte fatty acid compositions with FADS1 gene polymorphism in Japanese mothers and infants. (January 2020) - Nita, Reiko; Kawabata, Terue; Kagawa, Yasuo; Nakayama, Kazuhiro; Yanagisawa, Yoshiko; Iwamoto, Sadahiko; Kimura, Fumiko; Miyazawa, Teruo; Tatsuta, Nozomi; Arima, Takahiro; Yaegashi, Nobuo; Nakai, Kunihiko
Abstract: Long-chain polyunsaturated fatty acids (LC-PUFAs) are involved in the fetal growth in utero, and are essential for the development of visual and cognitive functions during infancy. The purpose of this study was to examine the associations of erythrocyte fatty acid compositions with FADS1 gene polymorphism in Japanese mothers and infants. The subjects were 383 mothers who participated in an adjunct birth cohort study of the Japan Environment and Children's Study (JECS). In maternal FADS1 SNP genotypes, the precursor fatty acids composition of the Δ5 desaturase in the maternal blood showed significant differences in levels among the groups, and showed increasing values in the order of TT < TC < CC genotype groups. On the other hand, many product fatty acids levels were significantly reduced in the order of TT > TC > CC genotype groups, and DHA levels were significantly lower in the CC genotype group relative to the other groups. Likewise, the relationship between fetal genotype group and fatty acid composition in cord blood was very similar to the maternal relationship. These results indicate the maternal and fetal blood fatty acid compositions are strongly influenced by the FADS1 genotypes. With respect to the cord blood DHA composition, the levels in the fetal CC genotype group showed a trend toward lower values in the maternal CC genotype group pair ( p = 0.066) compared to the maternal TC genotype group pair. However, in the fetal TT and TC genotype groups ( p = 0.131, p = 0.729, respectively), the maternal genotype did not have a significant effect. The DHA composition was more influenced by the maternal genotype in the fetal CC genotype group than in the fetal TT and TC genotype groups. It was shown that DHA transport via the placenta from the mother might be promoted in the fetal CC genotype compared to the other fetal genotype groups. In conclusion, differences in the FADS1 SNP genotypes of pregnant women and their children may greatly affect the supply of LC-PUFAs. Further studies on the involvement of the FADS1 polymorphisms and the fetal LC-PUFA levels in the fetal growth and development are warranted.